Language and Worldviews. (3rd July 2016) - Hewitt, Peter
Abstract : What is the relationship between language and the world it supposedly depicts? Is it possible to establish a straightforward correspondence between language and language independent facts, or does language in some way shape the way in which we see things? As natural languages seem to each have their own specific characteristics, as their vocabularies and grammars differ in significant respects, it seems impossible to establish a sphere of universally shared meaning. Meaning would seem to be embedded in the particular languages through which it is conveyed, but if that were the case, how would it ever be possible to understand another language or to translate from one language into another? Placing too much emphasis on the differences between languages would make understanding such differences impossible. Understanding is necessarily based on mutually shared concepts. On the other hand, if understanding is based on generally shared concepts, how is it possible to understand and convey the individual characteristics of a different language? There is thus an inevitable tension between the individual and general in languages, a tension that the hermeneutic tradition has attempted to address by affirming that it is possible for the various linguistic perspectives to find common ground through a dialogical approach to language that, it is hoped, would lead to a certain 'higher level' universality in which the different perspectives converge.